Understanding pelvic floor in women - Mittal, Rajni; Rath, Gayatri; Sahai, R. N.; Aggarwal, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Change from quadruped to erect posture has resulted in changes in the human pelvis. This has resulted in pelvis supporting the abdominal viscera. The bony pelvis is deficient on inferior aspect. Muscles covered by fascia on superior and inferior aspect. A good knowledge of pelvic floor is very basic and mandatory for any gynecologist as pelvic floor is crucial to support the pelvic organs and is required to maintain urinary and fecal continence.